The Hyperlipidaemic Drug Fenofibrate Significantly Reduces Infection by SARS-CoV-2 in Cell Culture Models - Davies, Scott P.; Mycroft-West, Courtney J.; Pagani, Isabel; Hill, Harriet J.; Chen, Yen-Hsi; Karlsson, Richard; Bagdonaite, Ieva; Guimond, Scott E.; Stamataki, Zania; De Lima, Marcelo Andrade; Turnbull, Jeremy E.; Yang, Zhang; et al. (Frontiers in Pharmacology, 2021)
The SARS-CoV-2 pandemic has caused a significant number of fatalities and worldwide disruption. To identify drugs to repurpose to treat SARS-CoV-2 infections, we established a screen to measure dimerization of ACE2, the primary receptor for the virus. This screen identified fenofibric acid, the active metabolite of fenofibrate. Fenofibric acid also destabilized the receptor binding domain (RBD) of the viral spike protein and inhibited RBD binding to ACE2 in ELISA and whole cell binding assays. Fenofibrate and fenofibric acid were tested by two independent laboratories measuring infection of cultured Vero cells using two different SARS-CoV-2 isolates. In both settings at drug concentrations which are clinically achievable, fenofibrate and fenofibric acid reduced viral infection by up to 70%. Together with its extensive history of clinical use and its relatively good safety profile, these studies identify fenofibrate as a potential therapeutic agent requiring urgent clinical evaluation to treat SARS-CoV-2 infection